2016
DOI: 10.1111/idj.12245
|View full text |Cite
|
Sign up to set email alerts
|

Emergency care provided in a Greek dental school and analysis of the patients’ demographic characteristics: a prospective study

Abstract: Services were requested primarily by individuals who were experiencing acute pain of endodontic origin, had low or no income and were available during morning hours, probably because of the service's low cost and operational hours. Prospective studies, such as the present investigation, can provide epidemiological evidence and indicate areas in the infrastructure of emergency services which may be improved. Additionally, such studies can provide rationale for public insurance programs and can generate profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
3
23
0
4
Order By: Relevance
“…Compared with previous publications addressing DE care, the population of the present study showed consistency regarding the gender ratio (1:1) and the most represented age class (18-29 years) [17][18][19]27,30 . Whereas previous studies provided a general description of subjects who attended the DE department 12,[17][18][19]21,27,30,31 , this study aimed to highlight profiles of patients by linking sociodemographic characteristics to care-seeking behaviours. Indeed, in the present study, the proportion of patients covered by CMU was almost two and a half times higher than the rate reported for this region in France 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous publications addressing DE care, the population of the present study showed consistency regarding the gender ratio (1:1) and the most represented age class (18-29 years) [17][18][19]27,30 . Whereas previous studies provided a general description of subjects who attended the DE department 12,[17][18][19]21,27,30,31 , this study aimed to highlight profiles of patients by linking sociodemographic characteristics to care-seeking behaviours. Indeed, in the present study, the proportion of patients covered by CMU was almost two and a half times higher than the rate reported for this region in France 32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that the lack of routine dental care leads to more emergency visits. Studies of patients who sought urgent care for acute dental problems in hospital emergency rooms and dental schools have revealed that these patients were generally uninsured or had low income . This same population has been highly correlated with a lesser likelihood of seeking regular dental care .…”
Section: Discussionmentioning
confidence: 52%
“…Studies of patients who sought urgent care for acute dental problems in hospital emergency rooms and dental schools have revealed that these patients were generally uninsured or had low income. [13][14][15] This same population has been highly correlated with a lesser likelihood of seeking regular dental care. 16 In medicine, however, there is much stronger evidence that correlates lower primary care provider continuity and increased rates of emergency department use in senior citizens, less compliance with physician recommendations, and more duplication of tests, examinations, and procedures.…”
Section: Discussionmentioning
confidence: 99%
“…1 The definition of "dental emergency" provided by the American Dental Association includes acute dental pain, and in the vast majority of cases the origin DENTAL MEDICINE // EMERGENCY MEDICINE of the pain is endodontic. 2 Dental emergencies include reversible and irreversible pulpitis, interappointment endodontic emergencies, dental trauma, periapical and periodontal abscess, cellulitis, pericoronitis and cracked tooth syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…2 Dental emergencies include reversible and irreversible pulpitis, interappointment endodontic emergencies, dental trauma, periapical and periodontal abscess, cellulitis, pericoronitis and cracked tooth syndrome. 1 The dense nerve network of the head and neck region is primarily responsible for the severity and intensity of the pain, which causes stress for both the patient and the clinician, and requires an immediate diagnosis and accurate treatment. 2 When establishing the therapeutic choice in the dental practice, the dentist will have to take two main aspects into account: the magnitude of the dental intervention and the potentially associated systemic pathology and its compensation level, which can allow or prevent safe dental therapy.…”
Section: Introductionmentioning
confidence: 99%